The Impact of Mindfulness Training on Occupational Stress and Quality of Life among Operating Room Personnel - Tina Soltanahmadi; Niloofar Rezaei; Hassan Shafaei; Tayebeh Khayatan (Journal of Modern Psychology)
Objective: This research demonstrates that the practice of mindfulness training led to a notable decrease in occupational stress and an improvement in the overall quality of life for professionals working in operating rooms.Methods: The method of the present research was practical in nature and quasi-experimental in the form of pretest-posttest with a control group. The statistical population of this research included all operating room experts in Tehran hospitals. 50 people from this community were selected by convenience sampling method and were randomly divided into two experimental (25 people) and control (25 people) groups. Data was collected using standard questionnaires. T tests and ANCOVA were used to analyze data. Results: The results showed that there is no significant difference in both occupational stress and quality of life in the pretest (both P>0.05). However, it was observed that experimental group had significantly lower occupational stress and higher quality of life compared to control group in the posttest (both P=0.001). Finally, the results of ANCOVA showed significant differences between experimental and control groups in both occupational stress and quality of life (both P=0.001).Conclusion: These findings indicate that mindfulness can play a crucial role in managing work-related stress among operating room experts. Consequently, by actively participating in mindfulness activities, it is plausible to create more favorable circumstances for professionals working in operating rooms in terms of their quality of life.